Temperature stressed males are less attractive to female red flour beetles - McNemee, Rachel; Marshall, Jeremy (My University, 2018)
Male red flour beetles (Tribolium castaneum) are shown to attract females through an aggression pheromone that may be altered due to varying degrees of stress (Wade, 1984). If these females do follow certain pheromone cues, then we would predict that they have a preference when given a choice between stressed and non-stressed males. This was tested by putting two sets of temperature stressed and non-stressed males in an arena with females and noting each interaction through a series of trials. By taking note of each mating, aggression, and simple encounter, we were able to find that females do prefer a non-stressed male. While stress can suppress multiple mechanisms in beetles, this sexual preference study provides insights into the reproductive processes of this pest and other invertebrates.
Keywords: Fall 2018